Washita [large type] - Rundell, B. N. (Rundell, B. N. McCain chronicles, 2025)
"As the relentless march of American expansion reaches the untamed West, the native peoples-burdened by the painful legacy of broken treaties and tumultuous history-simmer with distrust. While the younger generation of natives yearns to lay claim to their ancestral lands, the old chiefs are holding out for the elusive prospect of peace. Yet, when armed settlers continue to betray their promises time and again, even those who crave peace are inevitably pushed toward the precipice of bloodshed. Amidst this backdrop of turmoil, Elijah McCain finds himself reunited with his sons and surrounded by family. However, a new call to duty emerges when he's asked to lead the scouts of the formidable Colonel Forsyth and the enigmatic Colonel Custer. As McCain grapples with the dwindling allure of battle and the haunting question of loyalty, he stands at a crossroads."--